2021
DOI: 10.3390/ijerph182010818
|View full text |Cite
|
Sign up to set email alerts
|

Educational Programs for the Promotion of Health at School: A Systematic Review

Abstract: Context: Health promotion programs generate healthy changes in the educational community. However, not all of them meet the expected objectives due to multiple factors that affect their development, such as the teachers overload work, the lack of specific training, the lack of time to carry out health promotion activities, the lack of flexibility of the programs, and their non-inclusion in the training programs of the centers. Objective: To know the scope of the strategies and programs that promote healthy hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…In the school context, is essential knowing which interventions work, and it is also essential to understand how to implement them to obtain the benefits they propose, bearing in mind that schools are dynamic and heterogeneous contexts [ 35 ]. The program that is proposed in this research is a program based on the positive results that have been obtained in different areas of the application of Restorative Justice to resolve conflicts, thus, hypothetically, the intervention should be successful.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the school context, is essential knowing which interventions work, and it is also essential to understand how to implement them to obtain the benefits they propose, bearing in mind that schools are dynamic and heterogeneous contexts [ 35 ]. The program that is proposed in this research is a program based on the positive results that have been obtained in different areas of the application of Restorative Justice to resolve conflicts, thus, hypothetically, the intervention should be successful.…”
Section: Methodsmentioning
confidence: 99%
“…Education in peaceful conflict resolution is a process in which students receive lessons and practices on positive conflict management to facilitate the development of skills focused on dialogue. Some social-emotional learning programs, programs focused on values and respect, or programs that address specific problems such as bullying, teach how to manage conflicts in a harmonious and healthy way [ [31] , [32] , [33] , [34] , [35] ].…”
Section: Introductionmentioning
confidence: 99%
“…If VR effectively implements, it could revolutionize the way future healthcare professionals are trained in competencies for their promotion and in the confidence needed to face current challenges of work environment. (23,24,25) The methodology to be used will include both quantitative and qualitative analyses, ranging from controlled experiments to case studies and surveys. Differences be-tween traditional education and that incorporating VR Salud, Ciencia y Tecnología.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the authors of [16] proposed the adoption of alternative educational models developed for the early childhood education stage because studies [17][18][19][20][21] have found that they favor the promotion of well-being and the quality of life, personality development, and health and contribute significantly to the improvement of individual health and well-being [11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%